2015
DOI: 10.3732/ajb.1500255
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of induced defenses, growth, and reproduction in lima bean (Phaseolus lunatus) in response to multispecies herbivory

Abstract: Overall, this study highlights novel aspects of the specificity of plant responses induced by damage from multiple species of herbivores and uniquely associates such effects with plant lifetime fitness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 58 publications
1
53
0
Order By: Relevance
“…Our results showed that there is herbivore specificity of plant–plant communication, because herbivore resistance on receiver Baccharis salicifolia plants increased only when emitter and receiver plants were attacked by the same aphid species. Specificity of induced defences against herbivores has been found across several plant–herbivore systems (Agrawal, ; Bingham & Agrawal, ; Xiao et al ., ; Moreira et al ., , ; Rowen & Kaplan, ). Such specificity could have evolved by means of natural selection, and may thus be adaptive (Bingham & Agrawal, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that there is herbivore specificity of plant–plant communication, because herbivore resistance on receiver Baccharis salicifolia plants increased only when emitter and receiver plants were attacked by the same aphid species. Specificity of induced defences against herbivores has been found across several plant–herbivore systems (Agrawal, ; Bingham & Agrawal, ; Xiao et al ., ; Moreira et al ., , ; Rowen & Kaplan, ). Such specificity could have evolved by means of natural selection, and may thus be adaptive (Bingham & Agrawal, ).…”
Section: Discussionmentioning
confidence: 99%
“…We performed phenolic profiling according to Moreira et al . 33 . Briefly, we used ultrahigh-pressure liquid chromatography-quadrupole-time-of-flight mass spectrometry (UHPLC-QTOF-MS) to detect, identify and quantify phenolic compounds.…”
Section: Methodsmentioning
confidence: 99%
“…Induced resistance between different herbivore species has been shown in lima bean (Hernández‐Cumplido et al, ; Moreira et al, ) and other plant species (Agrawal, ; Rodriguez‐Saona et al, ). Given that parasitoids reduce the amount of damage by herbivores and change herbivore physiology, it is possible that induced resistance could be compromised by their presence.…”
Section: Discussionmentioning
confidence: 99%
“…Wild lima bean plants ( Phaseolus lunatus ) are naturally distributed along the Pacific coast from Mexico to South America (Freytag & Debouck, ). In our field site (see below), this annual legume germinates in June–July, produces flowers in October–November and seeds in December–January (Hernández‐Cumplido et al, ; Moreira et al, ). During the growing stage, lima bean plants are attacked by several leaf‐chewing insects, including the velvet armyworm Spodoptera latifascia (Lepidoptera: Noctuidae; Cuny et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation